Epiphytic medicinal plants as reliable sources of therapeutic agents with enhanced pharmacological activities - Umeyor, Ebuka; Umeyor, Immaculeta; Chukwuemerie, Ogechukwu; Ifejirika, Ezeonyi; Okoye, Festus (Journal of Current Biomedical Research, 2023)
Epiphytes are bioindicator groups of plant species that give important information on how the ecosystem support evolution of life in its habitat and to what extent this is achieved owing to their sensitivity and responsiveness to environmental stimuli. The plants have been used for the treatment of non-infectious and infectious diseases including boils, wounds, ulcers, smallpox, diarrhoea, fever, colds, ulcers, malaria, and worm infections. They are also used to improve hepatic functions, treat rheumatism, diabetes, bronchitis, and enhance muscle tone. Some of the novel bioactive molecules identified in epiphytes include flavanthrinin, nudol, and fimbriol. The pharmacological activities of epiphytes were discussed following information obtained from databases such as Google scholar, Science Direct, PubMed, Prota, Web of Science, Prosea, Scifinder Scholar, and Scopus. The review evaluated and discussed the ethnomedicinal uses of ten (10) epiphytes including Adiantum caudatum, Diaphananthe bidens, Nephrolepis cordifolia etc. The phytochemical factors of the plants (catechin, quercetin, kaempferol, alkaloids, and flavonoids) with their traditional uses were presented. Interestingly, these plants have shown significant medicinal properties including anticancer, antimicrobial, and anti-inflammatory activities.